Respostas

2013-11-27T18:13:34-02:00
A) x + y = 5
   x - y = 1
  2x = 6
x = 6/2
x= 3

x+ y = 5
3 + y = 5
y = 5 - 3
y = 2

b)  x + 2y = 7
    x   -  y = 1     x(2)

  x + 2y = 7
- 2x - 2y = 2

 -x =  9   x( -1)
 x = -9

x - y = 1
- 9 - y = 1
- y = 1 + 9
-y = 10       x( -1)
 y = -10


c) 3x + 4y = 13    x(-2)
    2x - 5y = 1       x(3)

 -6x - 8y = - 26
  6x - 10y = 3
       -18y = -23      x(-1)
        18y = 23
           y = 23/18

2x - 5y = 1
2x - 5 . 23/18 = 1
2x -115/18 = 1
2x= 1 + 115/18             mmc = 18
2x = 18 + 115  =  133  = 7,38
             18           18
x = 7,38/2
x= 3,69


    
   
 
 
2013-11-27T22:31:57-02:00
A)
x+y = 5
x-y = 1
-------------
2x = 6
x = 6/2
x = 3

3+y = 5
y = 5-3
y = 2

As outras são feitas de modo idêntico.